Soil Vegetation Relationship Studies in some Selected Tree Species of Mudumalai Forest Division - Singh, Jasbir; Gupta, G. N.; Prasad, K. G. (Indian Forester, 1988)
Present paper envisages information on the influence of climate, soil and topographic factors for the growth and distribution of three important tree species namely Anogeissus latifolia, Terminalia tomentosa and Tectona grandis in Mudumalai Forest Division of Tamil Nadu. T. tomentosa was found suitable in regions having > 1525 mm of annual rainfall, whereas A. latifolia and T. grandis performed well in the relatively lesser rainfall areas as well. T. tomentosa prefers very deep soils (> 120 cm) whereas good growth and density of T. grandis and A. latifolia were recorded on moderately deep soils. Density and growth of T. grandis was higher on medium textured soils whereas the density of A. latifolia was not affected by coarse textured soils. Higher growth and density of T. tomentosa was associated with poor P2O5 K2O and Mg contents of the soil. A. latifolia and T. grandis were found on soil rich in Ca and Mg. Soils rich in organic carbon and CEC occurred under better growth and density of teak.